The Clock Tower Ghost - Kemp, Gene (Penguin Group)
Amanda Phillips and the ghost of Addlesbury Tower, Rich King Cole, do frightful and funny things to each other, in their war to dominate the tower.
Keywords: Juvenile Fiction-Book